Production of glazed Kondol (Benincasa hispida) and papaya (Carica papaya) for dessert purposes - Carmona, Lester Anne C. (2010)
This study was conducted and focused in the production of glazed fruit though utilizing locally grown fruits such as kondol (Benincasa hispida) and papaya (Carica papaya). Three temperatures for osmotic dehydration were tested 30 degrees Celcius, 50 degrees Celcius, and 70 degrees Celcius to determine the optimal temperature for the glazing process. Among the three temperatures, 50 degrees Celcius was the optimal for glazed kondol and papaya. The developed products were subjected to Acceptability Test and analyzed using Sign Test as the statistical tool. The evaluation indicated that glazed kondol and papaya were acceptable. The developed products were also analyzed for its Moisture Content and Moisture Sorption Isotherm. The obtained MC value of glazed kondol and papaya were 43.70% and 41.86% respectively, which fall in the standard value of Intermediate Moisture Food and have a water activity of 0.82 to 0.84. Comparing the total costs of producing the developed products to the commercial glazed fruits, it was shown that the developed products can serve as a cheaper alternative.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Critical moisture content; Glazed fruit; Glazing processes; Kondol; Low density polyethylene; Moisture barrier; Moisture migration; Moisture sorption isotherm; Osmotic dehydration; Sign test; Fruits; Papaya; Desserts; Equilibrium Relative Humidity; Acceptability Test; Commercial glazed fruits; Intermediate Moisture Food